Microstructural Origins of the Corrosion Resistance of a Mg-Y-Nd-Zr Alloy Processed by Powder Bed Fusion – Laser Beam - Nilsson Åhman, Hanna; D’Elia, Francesco; Mellin, Pelle; Persson, Cecilia (Frontiers in Bioengineering and Biotechnology, 2022)
Magnesium alloys are biocompatible, biodegradable and have the ability to promote bone ingrowth, making them ideal candidate materials for replacing auto- and allografts in future treatments of large bone defects. Powder bed fusion – laser beam (PBF-LB) additive manufacturing of these alloys would further allow for the production of complex structures, optimized for bone grafting. However, the corrosion rates of structures processed by PBF-LB remain too high. An improved understanding of the influence of the microstructure generated during PBF-LB on the corrosion properties is considered key to their future implementation in implants. In this study, the effect of PBF-LB processing and subsequent hot isostatic pressing (HIP) on the microstructure and texture in different sample directions was studied and related to the corrosion behavior of a Mg-Y-Nd-Zr alloy. The results were compared with an extruded Mg-Y-Nd-Zr alloy. A higher amount of secondary phases resulted in a higher rate of localized corrosion for the PBF-LB processed material compared to that for the extruded one. Due to growth of the secondary phases, the corrosion rate was further increased after HIP. Moreover, a strong texture was observed in the PBF-LB material, and it was also enhanced in the HIP material. While this affected the electrochemical activity as measured by potentiodynamic polarization tests, any texture effect appeared to be masked by the contribution of the secondary phases in the longer-term mass change and hydrogen evolution tests. Future work should look further into the influence of individual process parameters on the microstructure and the resulting corrosion behavior of the material, to further clarify its interdependence.